Translation and adaptation of hearing handicap inventory for adult (HHIA) into Malay language: a pilot study - Tengku Zam Zam, Tengku Zulaila Hasma; Dzulkarnain, Ahmad Aidil Arafat; Rahmat, Sarah; Jusoh, Masnira (IIUM Press, 2017)
Introduction: Patient’s self-perceived handicap inventory is an important tool for modern’s health care management including hearing loss. The HHIA is a self-reporting outcome measurement invented to identify hearing-impaired patients’ complaints for appropriate client-centred rehabilitation program. HHIA has been reported among one of the valid self-perceived hearing handicap measures, and could even addressed issues for patient with mild and unilateral hearing loss. This study aims to translate HHIA into Malay language (HHIA-M) and to adapt the questionnaire culturally for clinical use among Malaysian population. Methods: Ten participants involved in this preliminary study. The questionnaire was initially translated using forward-backward techniques by four-panelists (2 panels for each level). The translated questionnaire was then reconciled and harmonized for cultural and content validations by the authors and two expert panels. Next, the harmonized version of the questionnaire was piloted among 10 hearing-impaired patients and 10 normal hearing participants for face and discriminant validation. All participants were recruited from IIUM Hearing and Speech Clinic. Results: The finding shows that the HHIA-M was easy to understand and took a short time to complete. Statistical analysis identified significant mean differences in HHIA scores between normal and hearing-impaired participants. Conclusions: This preliminary finding concluded that the HHIA-M has the potential to be an effective tool to evaluate the hearing handicaps among hearing-impaired patients in Malaysia and further study to investigate its psychometric property is warranted.